ARTIFICIAL BONE- AN OVERVIEW - Singh, Balveer (International Journal of Pharmaceutical & Biological Archive, 2016)
Replacement of extensive local bone loss is a significant clinical challenge. There are a variety of techniques available to the surgeon to manage this problem, each with their own advantages and disadvantages. It is well known that there is morbidity associated with harvesting of autogenous bone graft and limitations in the quantity of bone available. Alternatively allografts have been reported to have a significant incidence of postoperative infection and fracture as well as the potential risk of disease transmission. During the past 30 years a variety of synthetic bone graft substitutes has been developed with the aim to minimize these complications. The benefits of synthetic grafts include availability, sterility and reduced morbidity. The present article examines the relevance